Intra-uterine diazepam exposure decreases the number of catecholaminergic and serotoninergic neurons of neonate rats - da Silva Junior, Carlos Aparecido [UNESP]; Marques, Danuzia A.; Patrone, Luís Gustavo A. [UNESP]; Biancardi, Vivian; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier, 2023)
Benzodiazepines, such as diazepam (DZP), are used to treat anxiety disorders, and are prescribed to pregnant woman for therapeutic purposes. Concerns regarding their consequences on postnatal development rise as they cross the placenta and interact with the embryo. Occurrence of malformation and behavioral syndromes have been reported for different ages, but little is known about their effects on the brain after exposure during intrauterine life. Thus, we sought to evaluate the effects of intrauterine exposure to DZP on the number of brainstem's catecholaminergic and serotonergic neurons, implicated in respiratory control, in male and female rats on postnatal (P) day 12–13, using immunofluorescence labeling for tyrosine–hydroxylase (TH) and serotonin (5–HT). We observed a reduction in the number of catecholaminergic neurons for males and females. Special attention is given to the reduction in the density of neurons in the A6 region, involved in ventilatory responses to CO2. Interestingly, only males showed a reduction in the number of serotonergic neurons, while females were not affected. These findings suggest that in utero exposure to DZP results in deleterious neuroanatomical effects on P12–13 rats and raises a note of concern for women clinicians to make more informed choices about the use of anxiolytic treatments during gestation.
Keywords: Benzodiazepine; Breathing; Catecholamine; Critical period; GABA; Serotonin